Confidence Crises and Public Debt Management - Francesco Giavazzi; Marco Pagano (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1989)
The question that we ask in this paper is whether the danger of confidence crisis can be reduced by acting on the choice of the maturity structure of public debt.
Keywords: 330